You are not the father: rhetoric, settler colonial curiosity, and federal Indian law. Issue 1 (2nd January 2020) - Primack, Alvin J.
ABSTRACT: In this essay, the author uses Lacanian psychoanalytic theory to explain the specific insistence of blood and economic/personal financial relations as organizing signifiers in federal Indian law, taking Adoptive Couple v. Baby Girl (2013) as the primary case study of the author. The author maintains that Lacanian psychoanalysis helps clarify: (1) how these signifiers organize legal rhetorics through the notion of the unconscious; and (2) how the persistence of these signifiers reveals a broad structure of settler colonial curiosity that elucidates the link between federal Indian law's consistencies and instabilities. The author reasons that settler colonial curiosity is motivated by a curious attachment to the promises of an imaginary nation state as represented through signifiers, arguing that signifiers of blood and economic/personal financial relations function as shaky anchors in the discourse of federal Indian law. As shaky anchors, they draw upon centuries of public affective investment to feign a stability to federal Indian law while also leaving an opening for decolonial unsettling. The author concludes with some implications for psychoanalytic rhetorical criticism and Indigenous decolonial rhetorics.